Konstruksi Identitas Nasional Pada Masyarakat Adat: (Studi Kasus Di Kampung Naga Desa Neglasari Kecamatan Salawu Kabupaten Tasikmalaya) - Nurohman, Taufik; Gunawan, Hendra (Universitas Brawijaya, 2019)
This study examines the construction of national identity in indigenous peoples in Indonesia. This national identity is a form of social identity or collective identification which describes the attachment of group members to the state expressed with a sense of belonging, love, loyalty, pride, and protection of the group and its homeland. This national identity discourse is often an issue that is vulnerable to being discussed and debated in a society that has its own peculiarities such as indigenous peoples. These indigenous people have cultural identities, value systems and knowledge, living areas, and ways of interacting which are often different from other communities, so that they need different treatment in terms of building their national identity.